Does TikTok Social Media Increase Public Interest in the Seafarer Profession? - Mashudi Rofik; Ahmad Narto (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
The rise of videos on TikTok about life at sea has been led by many sailors who broadcast their lives. The extent to which the influence of TikTok videos affects people's interest in choosing a seafaring profession and entering a sailing school. In this study, we aim to investigate the impact of TikTok social media on the community related to interest in the seafarer profession. The mixed research method uses quantitative analysis and qualitative analyses. A quantitative study was carried out on students who participated in level 1 and 2 seafarer training in the Semarang area by providing a questionnaire through the Microsoft software Teams application, in March 2025, with a population of 126 people and based on the Krejcie & Morgan table with a confidence level of 95% with a sample of 95 respondents. Based on the results of quantitative and qualitative research, it was found that there was a strong relationship between the influence of TikTok videos on the public and the profession of seafarer. This study also shows that TikTok social media has become an effective platform in increasing public interest in the seafarer profession. Expand and enrich the literature review on the influence of social media, especially TikTok, on career choices, particularly in the context of the shipping profession, which has not been adequately explored.